EFFORTS TO IMPROVE THE PROCESS MATHEMATICS LEARNING AT MIN 49 BIREUEN - Anita, Anita (BRIGHT VISION Journal of Language and Education, 2022)
This study aims to analyze efforts to improve the process of learning mathematics at MIN 49 Bireuen. This study used a qualitative method and the subjects were taken by students of grades 3, 4, 5 and 6 MIN 49 Bireuen. Collecting research data using observation techniques, interviews, and documentation. This study concluded that the results of the interview process at the low and high grade levels were that many of them lacked understanding and lack of interest in learning mathematics at Madrasah Ibtidaiyah. The factors that hinder the process of learning mathematics, including the lack of interest and motivation of students towards learning and the methods used by the teacher are too monotonous so that it makes students less interested and excited to take part in the process of learning mathematics.